Difference in intracellular localization and expression level of recombinant rabies G-proteins of street virus (Kyoto strain) and fixed virus (CVS-26 strain) expressed in HEK293T cells - Hamamoto, N.; Kaku, Y.; Noguchi, A.; Morikawa, S.; Inoue, S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Virulence of rabies virus (RABV) has been mainly studied with fixed viruses (laboratory strains) having different degrees of pathogenicity, however, virulence is much different between fixed viruses and street viruses (wild strains). Highly attenuated fixed strains of RABV does not cause lethal infection with profound inflammation accompanied with apoptosis and neural degeneration in the central nervous system (CNS). Induction of innate immune responses in CNS is a hallmark of infection with highly attenuated strains, whereas neural damage is absent or minimal and innate immune responses are not induced in animals infected with street virus. In the street virus infected cells, intracytoplasmic virion maturation taken place in the ER/Golgi apparatus is commonly observed and budding of virus from cellular plasma membrane is less frequent than in the fixed virus infected cells. Since RABV G-protein is critical for induction of virus neutralizing antibody, profound expression and budding of virions on cellular surface in fixed virus infected cells might be a major target of the host immune system. Thus different pathogenicity between street virus and fixed virus might be associated with different localization of virion maturation. However, little is known about molecular mechanism of virion maturation both of fixed and street viruses. To elucidate this, we have expressed G-proteins of CVS-26 strain (fixed virus) and Kyoto strain (street virus) in HEL293T cells upon transfection of the pCAGGS (CXN2) plasmid bearing G-genes of CVS-26 and Kyoto strains, respectively. Intracellular expression and localization of G-protein of each strain was then examined by fluorescence antibody technique and Western blot analysis using anti-G mAb (No.#7-1- 9, kindly provided from Dr.Kawai). Confocal laser scanning microscopy showed CVS- 26 G-protein was mainly localized on plasma membrane, while Kyoto G-protein was predominantly localized at perinuclear membrane region. CVS-26 G-protein was shown to be expressed in abundance than Kyoto G-protein in HEK293T cells by Western blot analysis. These results indicate maturation site of infectious RABV solely determined by localization of Gprotein. Four amino acids in a signal peptide (SP) of G-protein of CVS-26 were distinct from those of Kyoto. The number of putative N-linked glycosylation sites was 3 and 2 on G-proteins of CVS-26 and Kyoto, respectively. Further analysis is required to elucidate whether these differences affect intracellular localization and expression level of RABV G-protein.